KESENJANGAN DIGITAL PADA KELUARGA JAWA DI KABUPATEN WONOSOBO - Lawang, Robert Markus Zaka; Meilani, Nur Laila; Puteri, Bunga Pertiwi Tontowi; Ekoriano, Mario (UNIVERSITAS SEBELAS MARET (UNS), 2021)
Advances in digital technology often have a negative impact on the quality of relationships between parents and children, especially adolescents in the family. The study aims to describe the responses of parents and adolescents in responding toward the digital divide in the javanese family structure. Theoretically, the digital divide is approached through Bourdieu's constructivism framework with the concept of digital capital as one of its derivatives. This study uses a quantitative descriptive approach. The survey of 225 parents and 225 adolescents in Kretek and Wonosobo sub-districts, in Wonosobo regency, was conducted using installed structured questionnaire in the Open Data Kit / ODK platform. Focus Group Discussion was conducted to further explore the survey findings. The results show that the digital divide in the family has fostered a culture of